2005
DOI: 10.1038/sj.tpj.6500312
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics Education: International Society of Pharmacogenomics Recommendations for Medical, Pharmaceutical, and Health Schools Deans of Education

Abstract: Pharmacogenomics would be instrumental for the realization of personalized medicine in coming decades. Efforts are evident to clarify the potential bioethical, societal, and legal implications of key pharmacogenomics-based technologies projected to be soon introduced into the core practice of medicine. In sharp contrast, a lack of sufficient attention to educational aspects of pharmacogenomics, both for professionals and for society at large, is evident. In order to contribute to this discussion, a 'Pharmacoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 34 publications
7
85
0
1
Order By: Relevance
“…Clearly, inadequate education both at undergraduate and postgraduate levels is a potential barrier to the widespread uptake of pharmacogenetic tests (Baars et al 2005;Newman and Payne 2008). In 2005, the International Society of Pharmacogenomics (ISP), recognizing this unmet need, published a number of recommendations, including one for undergraduate medical teaching of pharmacogenetics (Gurwitz et al 2005). They proposed that ''basic MD pharmacogenomics education should ideally encompass at least 4 h, and ideally about 8 h of teaching''.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, inadequate education both at undergraduate and postgraduate levels is a potential barrier to the widespread uptake of pharmacogenetic tests (Baars et al 2005;Newman and Payne 2008). In 2005, the International Society of Pharmacogenomics (ISP), recognizing this unmet need, published a number of recommendations, including one for undergraduate medical teaching of pharmacogenetics (Gurwitz et al 2005). They proposed that ''basic MD pharmacogenomics education should ideally encompass at least 4 h, and ideally about 8 h of teaching''.…”
Section: Introductionmentioning
confidence: 99%
“…2 The National Human Genome Research Institute (NHGRI) of the National Institutes of Health identified five core competencies with respect to pharmacogenomic educational needs for pharmacists: terminology, knowledge, interpretation, communication, and professionalism. 3,4 These core competencies have been endorsed by major health organizations, including the National Coalition for Health Professional Education in Genetics (NCHPEG), 4 the International Society of Pharmacogenomics, 5 the Accreditation Council for Pharmacy Education (ACPE), 2 American College of Clinical Pharmacy (ACCP), 7 the American College of Clinical Pharmacy (ACCP) Educational Affairs Committee, the American Society of Health-System Pharmacists (ASHP), 8 and the NIHfunded Genetic/Genomics Competency Center (G2C2). 2 Following these recommendations, multiple approaches describing the incorporation of pharmacogenomics in the education of health care providers have been published.…”
Section: Introductionmentioning
confidence: 99%
“…As well, because the definition of PGx was unknown to 18% of medical students in our study, our findings are in support of recommendations calling for more PGx teaching in the medical school curricula. 38 In the case of pediatric PGx testing, parents appeared to value their own understanding above their children' s. Because the concept of assent itself has different meanings in different contexts and jurisdictions, 42,43 the weight of a child' s assent should be also viewed in the context of the child's specific situation. Lastly, on issues besides assent, parents' views on personal PGx testing for themselves, including the acceptability of testing, were not markedly different from their views on PGx testing for their children.…”
Section: Discussionmentioning
confidence: 99%
“…38 Unlike other respondents, only medical students appeared to believe that GPs and specialists have different amount of expertise regarding PGx. In reality, it is known that there is great variability in physicians' familiarity with PGx.…”
Section: Figurementioning
confidence: 99%